Ship-based Trackline Geophysical Data (MGD77) from the Drake Passage acquired during the Nathaniel B. Palmer expedition NBP1208 (2012) (IEDA: Marine-Geo Digital Library, 2012)
This data set was acquired with a ship-based Gravimeter and Subbottom Profiler during Nathaniel B. Palmer expedition NBP1208 conducted in 2012 (Chief Scientist: Dr. Amy Leventer). These data files are of MGD77 format and include Bathymetry, Gravity (Field and Free Air Anomaly) data that were processed during the cruise.